Education and Cadre in Improving Knowledge of One Health in Elementary School-Age Children - Sari, Siti Shofiya Novita; Saputro, Sigit Ari; Qurniyawati, Eny; Yamani, Laura Navika; Astutik, Erni; Maulana, Firdausy Kurnia; Maghfiroh, Lailatul (Universitas Muhammadiyah Malang, 2024)
Purpose – Elementary school students can become agents of change so that education on the concept of One Health. The purpose of this community service is to increase knowledge about the concept of One Health in students and the regeneration of Little One Health Ambassadors at SDN Kalisari II Surabaya City. Design/methodology/approach – The method was counseling on the concept of One Health, and the selection of Little One Health Ambassadors. Activities were carried out in August-September 2023. The educational material was from One Health Lessons and have been adapted for children aged 8 - 10 years. One Health Ambassadors were selected based on the results of the assessment of poster work about One Health, and mastery of One Health material. Counseling activities on One Health education were carried out in the fourth and fifth grades with a total of 80 students. Findings – The results showed that the education provided can improve the knowledge of the target group about the concept of One Health (p-value = 0.003). The first winner of One Health ambassadors was chosen who indicated that he mastered the material about One Health and his work was the most interesting and could present it well. Originality/value – Community service activities produce changes that are by external targets.